2018
DOI: 10.1190/tle37100724.1
|View full text |Cite
|
Sign up to set email alerts
|

MASW applications for road construction and maintenance

Abstract: Road construction and maintenance are major parts of geotechnical engineering that deal with the stiffness of natural or manmade ground materials. At the earliest stage of new road construction, the ground along the planned route often needs to be characterized in terms of the overall stiffness of the overburden-bedrock system. During construction, multiple stages of compaction and grading of geotechnical materials occur, with each requiring stringent quality control processes to ensure necessary stiffness lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This reversal is explained by the decrease of velocities with the depth on the pavements. This interval [70 -200] was confirmed by the work of Park (2018) which showed that it is dependent on the length of the profile and the spread of the geophones. These results are also confirmed at various sites studied by Diene and Ndiaye (2022) with the same acquisition device.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This reversal is explained by the decrease of velocities with the depth on the pavements. This interval [70 -200] was confirmed by the work of Park (2018) which showed that it is dependent on the length of the profile and the spread of the geophones. These results are also confirmed at various sites studied by Diene and Ndiaye (2022) with the same acquisition device.…”
Section: Resultsmentioning
confidence: 81%
“…However, the use of the MASW method as a pavement investigation method remains tedious due to several implementation factors; This led to the use of peakless geophones with the Land Streamer acquisition technique [11] [12].…”
Section: Introductionmentioning
confidence: 99%